(3HZjI GdeQjO hCfS GdaQjO ajef ChdOg Ydi Hf eMeO Hf Ydi Hf GdQTjOs - (3YGeQ Hf eMeO Hf YHO Gddg Hf YGeQ Hf Ydj GdTgjO GdMSfj,J (B1135 (3g` s ((3eMeO Hf Ydi Hf UGdM GdNGdOi GdcjhGfi GdRjOi s)
(3ChdgG (B:s
(3GdMeO ddg GeG aEfg deG WQb SeYi ai HYV GHfGA GdSGOI GdCYdGe Ggd GdhbJ s
(3BNQgG (B:s
(3age eTGjN GdYdhe heQLM GdMdhe hEdjge jQLY YfO GdegeGJ hjSJfRd Hge GdNjQGJ hGdHQcGJ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B55s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B552 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B47 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs